PROGRAM PELATIHAN MANAJEMEN WAKTU DAN PEMBAGIAN TUGAS DIVISI VOLUNTEER DEVELOPMENT KOMUNITAS BINA ANTARBUDAYA CHAPTER JAKARTA - Handayani, Penny; Mokoginta, Karina Widyastuti; Larisa, Fransisca Indya; Han, Cheryl; Nainggolan, Julyanty Monalisa; Wiwanto, Raesyad Adhiatma (Jurnal Bakti Masyarakat Indonesia, 2025)
The training program targeted the Volunteer Development Division of the Bina Antarbudaya Community Chapter in Jakarta. Participants included three students from various disciplines. The program focused on time management and task division skills, aiming to enhance productivity and reduce conflicts. The implementation methods included questionnaires, interviews, and problem tree formation to identify the challenges faced. Specific tools like Google Calendar and Todoist were used to aid time management. The results of the training showed an improvement in time management and task coordination skills among division members. The number of meetings held according to schedule increased, and there was a reduction in internal conflicts related to scheduling. Post-activity evaluation using Google Form indicated a high level of satisfaction among division members with the new task management system. In conclusion, the training successfully enhanced efficiency and productivity within the Volunteer Development Division of the Bina Antarbudaya Community. It is recommended to continue integrating technology and time management skills training in community development programs.